ANALISIS KESULITAN MEMBACA PEMAHAMAN ISI BACAAN PADA PEMBELAJARAN TEMATIK INTEGRATIF PESERTA DIDIK KELAS IV - Dwi Putri Setianingsih; Sugiaryo Sugiaryo; Oktiana Handini (Widya Wacana: Jurnal Ilmiah, 2022)
Research objectives: 1) Knowing the difficulties of students in class IV SD Negeri Ketro 1 in understanding reading content 2) Knowing what factors influence students' difficulties in understanding reading content in integrative thematic learning 3) Knowing the efforts made to overcome students' difficulties in understanding reading content. The method used is descriptive qualitative research. The subjects used were class IV students and teachers. The source of the data obtained at Ketro 1 Public Elementary School was in the form of primary data obtained using interviews with fourth grade students and teachers, secondary data through observation, documentation. Observation data collection techniques, interviews, and documentation. Data analysis technique used descriptive qualitative interactive model. Conclusion: 1) Difficulty in reading comprehension of reading content in integrative thematic learning experienced by students in class IV SD Negeri Ketro 1 such as students having difficulty determining answers that are appropriate to the reading content and students not understanding the meaning of the reading content. 2) Factors that affect students' difficulties in understanding reading content in integrative thematic learning include lack of self-motivation, lack of interest in learning to read, and influence from friends. 3) Efforts are made to overcome difficulties in understanding reading content, namely by applying reading habits to students by carrying out reading activities in the library and teachers can use learning strategies or models namely Know Want Learn (KWL), which is a type of reading comprehension strategy to explore, gain information on reading content.